2017
DOI: 10.4067/s0719-38902017005002005
|View full text |Cite
|
Sign up to set email alerts
|

IMPLICANCIAS DE Campylobacter spp. COMO PATÓGENO ALIMENTARIO

Abstract: RESUMENCampylobacter spp. es un patógeno alimentario resistente a antibióticos. Es considerado como el primer agente etiológico de diarrea en humanos en los países desarrollados, y el segundo o tercero en países en vías de desarrollo. Las especies termotolerantes de Campylobacter son mundialmente reconocidas por generar la campilobacteriosis, una zoonosis asociada al consumo de alimentos de origen animal. El cuadro clínico generado por estas especies suele ser autolimitado, y la aplicación de un esquema antibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Although the most important source of infection worldwide is the consumption of undercooked poultry contaminated with Campylobacter or the mishandling of raw poultry products ( Mullner et al, 2009 ), other potential sources such as wild and domestic animals have been demonstrated ( Rukambile et al, 2019 ). The infectious dose of Campylobacter is 10 4 bacterial cells ( Mardones and López, 2017 ); however, lower infectious doses have been shown ( Wieczorek and Osek, 2013 ), which after multiplying in the small intestine, produce inflammation with infiltration of leukocytes in the intestinal lamina, resulting in the presence of leukocytes in the stool in 25–80% of cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the most important source of infection worldwide is the consumption of undercooked poultry contaminated with Campylobacter or the mishandling of raw poultry products ( Mullner et al, 2009 ), other potential sources such as wild and domestic animals have been demonstrated ( Rukambile et al, 2019 ). The infectious dose of Campylobacter is 10 4 bacterial cells ( Mardones and López, 2017 ); however, lower infectious doses have been shown ( Wieczorek and Osek, 2013 ), which after multiplying in the small intestine, produce inflammation with infiltration of leukocytes in the intestinal lamina, resulting in the presence of leukocytes in the stool in 25–80% of cases.…”
Section: Introductionmentioning
confidence: 99%
“…Campylobacteriosis constitutes an important public health problem due to the increase in its occurrence, new forms of transmission, increased resistance of microorganisms to antibiotics and the socioeconomic impact they cause. Furthermore, it is associated with multiple gastrointestinal conditions, including inflammatory bowel diseases (IBD), Barrett’s esophagus, and colorectal cancer ( Mardones and López, 2017 ). In some cases, extra gastrointestinal manifestations may develop, including bacteremia, lung infections, brain abscess, meningitis, and reactive arthritis ( Kaakoush et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Supported by studies showing that Campylobacter spp. can survive at refrigeration temperature in different biological environments for long periods, through adaptive responses to cold [ 10 , 81 , 82 ]. Studies have shown a correlation between environmental temperature and the number of cases.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that an inoculum of 10 4 cells is sufficient for infection by Campylobacter spp. to occur, and in some cases, Campylobacter spp., is highly infectious, giving rise to disease with only 500 cells depending on the strain, damage to the cells by a stressful environment and host susceptibility (Hunt Jan, Abeyta & Tran, 2001;Mardones P. & Lopez-Martin, 2017). Campylobacteriosis is characterized by symptoms such as diarrhea, which is generally bloody, abdominal pain, dehydration, weakness, malaise, fever, headache, nausea and/or vomiting that appears between 5 and 10 days after infection with a usual duration of 3 to 6 days; mortality is low but occurs in a greater proportion in groups considered high-risk populations, such as children, elderly, and people with chronic conditions and immunosuppressed systems.…”
Section: Campylobacter Generalitiesmentioning
confidence: 99%
“…The indiscriminate use of antibiotics in humans (clinical) and in animal production has been established as protective or preventive, therapeutic and growth promoting, resulting in the emergence and spread of antibiotic resistance among various pathogens, including Campylobacter spp., in areas involved in animal production for food (mainly in poultry) and the environment. This resistance can, therefore, be transmitted through food production and consumption, becoming a global risk for human health (Epps et al, 2013;Mardones P. & Lopez-Martin, 2017;Wieczorek & Osek, 2013). To control this phenomenon in microorganisms, action plans, strategies, guidelines, recommendations and codes of practice have been developed at the global level by the World Health Organization (WHO), the United Nations Food and Agriculture (FAO)-Codex Alimentarius and the World Organization for Animal Health (OIE) with the aim of promoting best practices that reduce or control the emergence and spread of antimicrobial resistance through the optimal use of these compounds in human and animal health, with regulations for the use of medicine and waste management, as well as in the production of food with good hygiene practices in the agricultural, livestock, and aquaculture sector, which are considered key to achieving food safety and combating resistance to antimicrobials (FAO, 2018; WHO, 2018b).…”
Section: Resistance To Antimicrobialsmentioning
confidence: 99%